Genome‐resolved viral and cellular metagenomes revealed potential key virus‐host interactions in a deep freshwater lake. (6th November 2019) - Okazaki, Yusuke; Nishimura, Yosuke; Yoshida, Takashi; Ogata, Hiroyuki; Nakano, Shin‐ichi
Summary: Metagenomics has dramatically expanded the known virosphere, but freshwater viral diversity and their ecological interaction with hosts remain poorly understood. Here, we conducted a metagenomic exploration of planktonic dsDNA prokaryotic viruses by sequencing both virion (<0.22 μm) and cellular (0.22–5.0 μm) fractions collected spatiotemporally from a deep freshwater lake (Lake Biwa, Japan). This simultaneously reconstructed 183 complete (i.e., circular) viral genomes and 57 bacterioplankton metagenome‐assembled genomes. Analysis of metagenomic read coverage revealed vertical partitioning of the viral community analogous to the vertically stratified bacterioplankton community. The hypolimnetic community was generally stable during stratification, but occasionally shifted abruptly, presumably due to lysogenic induction. Genes involved in assimilatory sulfate reduction were encoded in 20 (10.9%) viral genomes, including those of dominant viruses, and may aid viral propagation in sulfur‐limited freshwater systems. Hosts were predicted for 40 (21.9%) viral genomes, encompassing 10 phyla (or classes of Proteobacteria) including ubiquitous freshwater bacterioplankton lineages (e.g., Ca . Fonsibacter and Ca . Nitrosoarchaeum). Comparison with viral genomes derived from published metagenomes revealed viral phylogeographic connectivity in geographically isolated habitats. Notably, analogous to their hosts, actinobacterial viruses were among the most diverse, ubiquitous and abundant viral groups in freshwater systems, with potential high lytic activity in surface waters.